Pediatric pulmonology year in review 2016: Part 2. Issue 9 (25th April 2017) - Auten, Richard; Ren, Clement; Yilmaz, Ozge; Noah, Terry L.
Abstract: Pediatric Pulmonology continues to publish research and clinical topics related to the entire range of children's respiratory disorders. As we have done annually in recent years, we here summarize some of the past year's publications in our major topic areas, as well as selected literature in these areas from other core journals relevant to our discipline. This review (Part 2) covers selected articles on neonatology, asthma, physiology and lung function testing, and infectious diseases.